Improved serodiagnosis of Lyme disease. Issue 2 (April 1996) - Davidson, M M; Chisholm, S M; Wiseman, A D; Joss, A W L; Ho-Yen, D O
Abstract : Aims —To determine whether enzyme linked immunosorbent assay (ELISA) results for Borrelia burgdorferi require confirmation by immunoblotting and how immunoblotting may best be used in the diagnosis of Lyme disease. Methods —Over one year, all referrals for Lyme disease to a district general hospital with a large tick population in its catchment area were tested by ELISA. Positive, low positive and negative serum samples were subjected to immunoblotting and the reactive bands analysed. Results —In total, 633 samples were received; 38 were ELISA positive and 97 low positive. More serum samples were from rural (n = 356) than from urban (n = 277) areas but a higher percentage of serum samples from urban areas were ELISA positive. The ELISA results were confirmed by immunoblotting in 15/38 positive samples but in only four of 37 with a low positive titre. An IgM positive blot required a 41 kDa band plus ≥1 specific band; for IgG a 41 kDa band plus ≥2 specific bands were necessary. Five serum samples were IgM positive with a 41 kDa plus one or more other specific bands. For IgG blots, the best discrimination was seen with the 21, 31, 46, and 92 kDa bands. Nonspecific, weakly reacting bands at 55, 60 and 67 kDa were frequently seen. Infection was confirmed in four of six patients with arthritis, but in only one of 10 patients with erythema chronicum migrans. Conclusions —ELISA alone is insufficient for diagnosis. All positive and low positive or negative serum samples with a good clinical history should be examined by immunoblotting. A higher percentage of modified ELISA positive than low positive results were confirmed. There are significant differences between European and American immunoblotting patterns. Local results show similarity to American results, highlighting the need for a local Borrelia isolate.